Why is civil conflict path dependent? A cultural explanation - Atin Basuchoudhary (Games, 2021)
Empirical investigation suggests that conflict is path-dependent, i.e., current conflict leads to more conflict in the future. However, there is very little formal theory for why conflict path dependence exists. We propose a mathematical model to explore one possible pathway to explain the persistence of conflict once it starts. In this model, there are three types of cultures in two boundedly rational populations. The two populations are State Actors and Insurgents. The three cultures are Peaceable, Warring, or Bargainers. The distribution of these types is different in each population. Evolutionary dynamics determine which of these three cultures might predominate. Our simulations suggest that it is rational for people to learn to be warlike even in environments where State Actors are willing to give large side payments to "buy" peace to avoid bargaining failure. War can also be learned when State Actors and Insurgents are extremely patient and, therefore, potentially committed to Pareto improving peace deals. The outcomes of these simulations suggest that cultural learning can be a hitherto ignored explanation for why conflict is path dependent. If culture is indeed a possible cause for conflict, the best intentions of technocratic peacemakers trying to build frameworks for resource sharing and/or institutional building may fail, simply because such structures are not suited to local conditions. On the flip side, our model also provides theoretical reasoning for the observation that conflict is not a deterministic outcome of bargaining and commitment failures.
Keywords: 330; civil conflict; civil war persistence; evolutionary game theory; length of civil wars; path dependence